2014
DOI: 10.1080/19443994.2013.865566
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption capacity of methylene blue, an organic pollutant, by montmorillonite clay

Abstract: The isotherms and kinetics of the adsorption of a cationic dye in aqueous solution, methylene blue, on a local Algerian montmorillonite clay mineral (raw, sodium and thermally activated at 300 and 500˚C) were determined experimentally. Various parameters influencing the adsorption were optimized, mainly solid-liquid contact time, mass of adsorbent, initial concentration of dye, pH of the solution and temperature. Results showed that the adsorption kinetics were fast: 30 min for the raw clay mineral, and 20 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 31 publications
4
26
0
Order By: Relevance
“…Further, the capacity of the material to act as a filter against organic and emerging pollutants such as methylene blue and sodium dodecyl sulfate [34,35] is evaluated and reported in Figure 8. It was observed that the foams are able to recover from 42% to 55% of methylene blue and from 15% to 27% of SDS.…”
Section: Extrinsic Chemical Propertiesmentioning
confidence: 99%
“…Further, the capacity of the material to act as a filter against organic and emerging pollutants such as methylene blue and sodium dodecyl sulfate [34,35] is evaluated and reported in Figure 8. It was observed that the foams are able to recover from 42% to 55% of methylene blue and from 15% to 27% of SDS.…”
Section: Extrinsic Chemical Propertiesmentioning
confidence: 99%
“…Therefore, the suitability of low-cost and renewable adsorbents, particularly clay-based derivatives has drawn great attention for the remediation of toxic pollutants [9]. Of major interest, montmorillonite has been proposed to be a good candidate [10], evidence from the intercalation of water pollutants by the modification of d(0 0 1) reflection [11][12][13][14][15][16].…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…The shift in the intercalated montmorillonites was related to the local environment of the interlayer space. Results indicated the 1-3 ppm upfield chemical shift for the end-methyl (δC16 ) and methylene (δC15 , δC[2][3][4][5][6][7][8][9][10][11][12][13][14] …”
mentioning
confidence: 99%
“…Good removal capability of clay materials to uptake dye was previously demonstrated by Bagane and Guiza [53], Harris et al [54], Ghosh and Bhattacharyya [55], Espantaleon et al [56], Al-Ghouti et al [57], Shawabkeh and Tutunji [58], Atun and Hisarli [59], Ozdemir et al [60], Özcan et al [61], and Tsai et al [62], and more recently by Demirbas and Alkan [63], Feddal et al [64], and Vanaamudan et al [65]. For instance, the removal performance of Fuller's earth and CAC for Basic Blue 9 was compared by Atun and Hisarli [59].…”
Section: Claysmentioning
confidence: 84%